2019
DOI: 10.1016/j.cell.2018.11.035
|View full text |Cite|
|
Sign up to set email alerts
|

Recirculating Intestinal IgA-Producing Cells Regulate Neuroinflammation via IL-10

Abstract: Plasma cells (PC) are found in the CNS of multiple sclerosis (MS) patients, yet their source and role in MS remains unclear. We find that some PC in the CNS of mice with experimental autoimmune encephalomyelitis (EAE) originate in the gut and produce immunoglobulin A (IgA). Moreover, we show that IgA + PC are dramatically reduced in the gut during EAE, and likewise, a reduction in IgA-bound fecal bacteria is seen in MS patients during disease relapse. Removal of plasmablast (PB) plus PC resulted in exacerbated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
162
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 274 publications
(165 citation statements)
references
References 50 publications
3
162
0
Order By: Relevance
“…To this end, a recent study showed that serum IgA from individuals with T1D has a differential ability to bind specific bacteria compared with that from healthy controls (25). Furthermore, IL-10 production from recirculating intestinal IgA + B cells protected mice from developing autoimmune encephalomyelitis (26). Thus, both IgA + B cells and secreted IgA have important roles in mediating gut homeostasis and the susceptibility to autoimmunity.…”
Section: Introductionmentioning
confidence: 99%
“…To this end, a recent study showed that serum IgA from individuals with T1D has a differential ability to bind specific bacteria compared with that from healthy controls (25). Furthermore, IL-10 production from recirculating intestinal IgA + B cells protected mice from developing autoimmune encephalomyelitis (26). Thus, both IgA + B cells and secreted IgA have important roles in mediating gut homeostasis and the susceptibility to autoimmunity.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of publicly available ChIP-seq datasets in both murine and human B cells are in line with this finding, suggesting that IL-10 is a significantly enriched target of BLIMP1 32,45 . This observation is reminiscent of recent 305 work highlighting the role for BLIMP1-expressing regulatory plasmablasts and plasma cells in vivo 3,4,46,47 , but also in humans ex vivo 47 . Whilst this previous work provided a correlative link between BLIMP1 and IL-10, we suggest that BLIMP1 is a direct regulator of IL-10 in B cells.…”
mentioning
confidence: 61%
“…Immunosuppressive B cells form a critical component of the immune regulatory compartment 1,2 . It is thought that their suppressive capacity derives mainly from their ability to produce IL-10, and in the absence of any lineage marker, this is considered a hallmark of regulatory B cells [3][4][5][6] . Their functional importance has been well described in murine models of disease, demonstrating a potent regulatory capacity across a number of contexts including infection, cancer, and autoimmune disease 3,[7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, an underrepresentation of Lachnospiraceae at the family level and Bifidobacterium and Lactobacillus at the genus level has been described in depressed cohorts (Naseribafrouei et al, 2014;Jiang et al, 2015;Aizawa et al, 2016). Interestingly, probiotics are effective in reducing depressive symptoms and microbiome transfers from depressed human patients into rats were sufficient to induce depressive-like behaviors in the animals, further supporting the idea that the microbiome can initiate depression (Kelly et al, 2016;Rojas et al, 2019). However, gaps remain in our understanding of how the gut-brain axis contributes to depression.…”
Section: The Gut-brain Axis In Depressionmentioning
confidence: 96%